Tapasin-mediated editing of the MHC I immunopeptidome is epitope specific and dependent on peptide off-rate, abundance, and level of tapasin expression - Boulanger, Denise S. M.; Douglas, Leon R.; Duriez, Patrick J.; Kang, Yoyel; Dalchau, Neil; James, Edd; Elliott, Tim (Frontiers in Immunology, 2022)
Tapasin, a component of the major histocompatibility complex (MHC) I peptide loading complex, edits the repertoire of peptides that is presented at the cell surface by MHC I and thereby plays a key role in shaping the hierarchy of CD8+ T-cell responses to tumors and pathogens. We have developed a system that allows us to tune the level of tapasin expression and independently regulate the expression of competing peptides of different off-rates. By quantifying the relative surface expression of peptides presented by MHC I molecules, we show that peptide editing by tapasin can be measured in terms of “tapasin bonus,” which is dependent on both peptide kinetic stability (off-rate) and peptide abundance (peptide supply). Each peptide has therefore an individual tapasin bonus fingerprint. We also show that there is an optimal level of tapasin expression for each peptide in the immunopeptidome, dependent on its off-rate and abundance. This is important, as the level of tapasin expression can vary widely during different stages of the immune response against pathogens or cancer and is often the target for immune escape.